Odpowiedzialność nieletnich za przestępstwa skarbowe i wykroczenia skarbowe - Sawicki, Janusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article reviews the most significant issues associated with the applicable model of juvenile liability as set out in the Act on Juvenile Delinquency Proceedings and the Criminal Code. The study focuses on juvenile liability for fiscal offences defined in the Fiscal Criminal Code, providing conclusions and suggesting changes in the way minors are treated in Poland in this particular respect, which may contribute to the development of a proper solution to the problem in the future.
Keywords: nieletni; przestępstwo skarbowe; wykroczenie skarbowe